1998
DOI: 10.1007/bf02464799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lesioning of the parafascicular nucleus of the thalamus on an operant food-procuring reflex in rats

Abstract: Studies have demonstrated that lesioning of the parafascicular nucleus, a member of the caudal group of intralaminar nuclei, worsens performance of defensive reflexes [ 1, 2]. Degradation of the parafascicular nucleus has been shown [2] to have no effect on simple types of food-procuring contextual reflexes, while complex types of these reflexes (selection tasks, complex mazes) are irreversibly damaged. Thus, the question of the possible mechanisms by which the parafascicular nuclei of the thalamus are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Resolution of the contradiction between food-procuring reflexes was addressed by using a modified method including consideration of the strength of pedal pressing, with provision of reinforcement only when pressing was stronger. Experiments conducted using this approach showed that lesioning of the Pf nucleus of the thalamus led to decreases in the strength of pedal-pressing and increases in the numbers of weak presses over seven days of testing after surgery [5]. However, the simultaneous roles of the Pf nucleus of the thalamus and the cholinoreactive system of the neostriatum in controlling food-procuring reflexes at different stages of training in rats remain unclear.…”
mentioning
confidence: 97%
“…Resolution of the contradiction between food-procuring reflexes was addressed by using a modified method including consideration of the strength of pedal pressing, with provision of reinforcement only when pressing was stronger. Experiments conducted using this approach showed that lesioning of the Pf nucleus of the thalamus led to decreases in the strength of pedal-pressing and increases in the numbers of weak presses over seven days of testing after surgery [5]. However, the simultaneous roles of the Pf nucleus of the thalamus and the cholinoreactive system of the neostriatum in controlling food-procuring reflexes at different stages of training in rats remain unclear.…”
mentioning
confidence: 97%